Screens, maps & networks: from genome sequences to personalized medicine - Sandmann, Thomas; Boutros, Michael (Current opinion in genetics & development, 2012)
Genome sequencing of tumors provides a wealth of information on mutations and structural variations, instilling hope that this data can be used to predict individual tumor progression and response to treatment. Yet currently, our ability to predict the functional consequences of these aberrations remains poor. How do cancer-associated mutations give rise to the hallmark phenotypes of cancer? Recently, information about the genetic makeup of cancer cells has been combined with novel functional genomics approaches to identify novel targets, exploit synthetic lethality and explore the rewiring of cellular pathways. Here, we highlight recent developments revealing the hidden landscape of genetic interactions in model organisms and cancer cells, a key step toward personalized cancer diagnostics and therapy.